"I'm Trying to Give Them My Face." Everyday Embodied Agency of the Muslim Other in Amsterdam. Issue 1 (14th November 2021) - Shaker, Reza; van Lanen, Sander; van Hoven, Bettina
Abstract : Focusing on the Muslim Other in Amsterdam, the article explores how individual young Muslims embody their agency in the forms of micro‐practices and socio‐spatial relations. By highlighting the spatio‐corporeal aspects of Muslims' presence within urban space, our ethnography foregrounds how young Muslims negotiate identities and belonging within everyday urban spaces of encounter. Dealing with the everyday panoptical white Othering gaze, we describe a range of "unremarkable" ordinary practices and everyday small agencies that young Muslims in Amsterdam adopt including invisibility, challenging whiteness, and accumulating whiteness.